PERINTAH MEMBUNUH ANJING DALAM HADIS: STUDI ATAS PEMIKIRAN IMAM AL-HARAMAIN - Repa Hudan Lisalam; Hapizul Ahdi (Jurnal Studi Hadis Nusantara, 2023)
This article discusses the thoughts of Abd al-Malik Ibn Abdillah Abu Ma'ali al-Juwaini or better known as Imam Haramain in addressing the hadiths which contain orders to kill dogs. The aim is to find out the method used by Imam Haramain in understanding and positioning these hadiths because the instructions for the pronunciation are different and seem to contradict each other. Some hadiths absolutely command dogs, some others only order to kill black dogs and some contain praise for the person who saved the dog's life. The method used in this article is library research. The result of this study is that the method used by Imam Haramain in addressing the hadiths containing the order to kill the dog is al-naskh wa al-mansukh, namely by making the hadith that comes later as an eraser of the contents of the hadith that appears earlier. Regarding the hadith which contains the order to kill a dog, there are at least two processes of al-naskh wa al-mansukh. First, an order to kill a dog is absolutely abolished by an order to kill a black dog only. Second, the order to kill black dogs was abolished by the permissibility of killing dogs that were dangerous to humans. Imam Haramain finally concluded that only dogs that had the potential to harm humans could be killed. Thus, feelings of disgust because of the dog's condition as unclean or because the dog is black is not necessarily a reason for muslims to torture or kill dogs.